2018
DOI: 10.1002/art.40520
|View full text |Cite
|
Sign up to set email alerts
|

Review: What Is the Current Evidence for Disease Subsets in Giant Cell Arteritis?

Abstract: Giant cell arteritis (GCA) is an autoimmune vasculitis affecting large and medium‐sized arteries. Ample evidence indicates that GCA is a heterogeneous disease in terms of symptoms, immune pathology, and response to treatment. In the current review, we discuss the evidence for disease subsets in GCA. We describe clinical and immunologic characteristics that may impact the risk of cranial ischemic symptoms, relapse rates, and long‐term glucocorticoid requirements in patients with GCA. In addition, we discuss bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 99 publications
(163 reference statements)
5
39
0
Order By: Relevance
“…Patients with overlapping disease also had a high prevalence of laboratory abnormalities and constitutional symptoms. Similar to prior studies , patients with LV involvement, including those with overlapping disease, were less likely than patients without LV involvement to have visual changes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Patients with overlapping disease also had a high prevalence of laboratory abnormalities and constitutional symptoms. Similar to prior studies , patients with LV involvement, including those with overlapping disease, were less likely than patients without LV involvement to have visual changes.…”
Section: Discussionsupporting
confidence: 83%
“…With the widespread adoption of vascular imaging into clinical practice, clinical variability among patients with GCA is increasingly being recognized. Previous studies have shown that patients with GCA can differ in their systemic inflammatory response, extent of arterial involvement, and treatment response , and suggest that there are distinct subgroups of GCA with potentially divergent disease etiology. Identifying subgroups may lead to stratified clinical decision‐making and enable research into differences in disease pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular ischaemia is a feared complication of GCA 1. Laboratory testing often reveals systemic inflammation, that is, high C-reactive protein (CRP) levels, anaemia and thrombocytosis 2…”
Section: Introductionmentioning
confidence: 99%
“…temporal headache, scalp tenderness and jaw claudication) before considering a GCA diagnosis, although these "classic" symptoms are by no means universal in GCA [7]. A recent clinical review by van der Geest et al classified GCA as a clinically and immunologically heterogeneous autoimmune disease, dividing it into three subsets: (i) systemic inflammation, (ii) vasculitis of large systemic arteries and (iii) polymyalgia rheumatica [8]. Related to the specific outcome of visual loss, studies have suggested that the risk of visual loss is higher in GCA patients with symptoms such as jaw claudication and in patients who do not have the typical temporal headache [2].…”
Section: Introductionmentioning
confidence: 99%